Pre-stack time-migrated seismic profile ATLANTIS-I, 31N Central Atlantic - César R Ranero; Arantza Ugalde; Laura Gómez de la Peña; Manel Prada (PANGAEA, 2024)
Pre-stack time-migrated seismic section across ATLANTIS-I profile in 2022 at 31N Central Atlantic. The seismic data were acquired with a seismic source that consisted of two sub-arrays of airguns with total capacity of ~4000 c.i., towed from the stern of the boat at 15 m of depth, and fired every 100 m. Seismic data were collected with a 240-channel, 3-km-long streamer towed from the stern of the boat at 19 m of depth. Data processing included streamer geometry for common mid-point geometry, a two-window statistical Wiener deconvolution, velocity analysis every 5 km, stacking, and time migration using a finite-differences algorithm and a geological meaningful Vp model. Final display is shown with a Butterworth minimum phase band pass filter (3-60 Hz) and a median automatic gain control (AGC) with a 2 second sliding window to balance amplitudes.